Develop a curriculum for first-year students at Aksu vocational and technical college’s school of humanities and arts, focusing on teaching Chinese folk songs - Luo, Yali; Onlamul, Kritsakorn (Asian Journal of Contemporary Education, 2024)
This research investigates the integration of Chinese folk songs into the curriculum at Aksu Vocational and Technical College, situated in the culturally diverse Aksu region of Xinjiang, China. This study identifies significant gaps in current music education methods, particularly the disconnect between theoretical learning and practical application, which hinders students’ ability to engage deeply with the material and develop employable skills. Employing a mixed-methods research design, both qualitative and quantitative approaches were used to develop, implement, and evaluate a teaching package specifically designed for first-year students. The package aimed to enhance students’ understanding and appreciation of Chinese folk music, thereby improving their cultural competence and engagement with the academic content. The findings suggest that the new curriculum significantly boosted the students’ knowledge of and connection to folk music traditions. It also facilitated a better understanding of the music’s historical, cultural, and social contexts. Moreover, the teaching package fostered essential skills in cultural awareness and academic involvement, contributing effectively to vocational music education in a multi-ethnic setting. This approach not only bridges the gap between theory and practice but also enriches the students’ educational experience by embedding cultural appreciation into the learning process, making a substantial contribution to the field of music education.